Analysis Of Factors Associated With The Use Of Postpartum Family Planning - Rini Indrawati; Elisa Ulfiana; Ngadiyono (Jurnal Profesi Bidan Indonesia, 2022)
Background; Postpartum Family Planning (KBPP) is a family planning service that is given to couples of childbearing age after delivery for up to 42 days, with the aim of ending fertility. The impact of the low use of postnatal contraception is that it can lead to unwanted pregnancies. Factors related to the use of family planning are individual characteristics and knowledge. Objective: This study to determine the factors associated with the use of postpartum family planning at Pamotan Health Center, Rembang Regency. Methods: This study was an analytic with a retrospective research design. The population in this study were all mothers who gave birth at the Pamotan Health Center. Sampling technique with total sampling so that the sample size is 40 people. The research instrument used a questionnaire. Data analysis using Chi Square test. Results: The age at most not at risk was 65%, the most education was high school 72.5%, the most parity was multipara 55%, the most knowledge was good 75%, the most use of family planning uses 80% family planning. Factor analysis of post-partum family planning use on age obtained pvalue 0.034 (0.5-0.89), education got p-value 0.000, parity got p-value 0.005 (1.146-2.15), knowledge got p-value 0.000. Conclusion: Factors related to the use of family planning are age, education, parity and knowledge.